Comparative Study of Micro-Bone Window and Conventional Bone Window Microsurgery for Hypertensive Intracerebral Hemorrhage. Issue 4 (June 2020) - Shao, Xuefei; Wang, Qifu; Shen, Jun; Liu, Jiaqiang; Chen, Sansong; Jiang, Xiaochun
Abstract : Objective: To compare and analyze the efficacy and safety of traditional craniotomy and small bone window craniotomy in the treatment of hypertensive cerebral hemorrhage (HICH). Patients and Methods: Fifty-four patients with HICH treated with traditional craniotomy and small bone window craniotomy were retrospectively analyzed. The operation time, hospitalization time, preoperative, and postoperative CT analysis, Glasgow coma scale (GCS) score and Glasgow outcome scale (GOS) scores were analyzed. Results: There were no significant differences in gender, age, hematoma volume, GCS score and pre-operative time between the 2 groups ( P   >  0.05). The operation time and hospitalization time of the micro-bone window group were shorter than those of the traditional operation group (P   <  0.05). The GCS and GOS scores of the small bone window group after 3 days and 6 months were higher than those of the traditional operation group ( P   <  0.05). However, there was no significant difference in hematoma clearance rate, re-bleeding rate and infection rate between the two groups (P   >  0.05). Conclusion: For patients with GCS 8–12 HICH, micro-bone window not only has the same effect as traditional bone window, but also has the advantages of shorter operation time and less trauma. Abstract : Supplemental Digital Content is available in the text